1991
DOI: 10.1515/cclm.1991.29.6.375
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Coagulation and Fibrinolysis Factors and Platelet Function in Hypertension

Abstract: Summary:Fifty-one patients with mild hypertension were evaluated in relation to the plasma concentrations of coagulation and fibrinolysis factors äs well äs for the aggregability of their platelets.In a considerable number of the patients (18/51), a significantly enhanced in vitro ADP aggregation was found. In the coagulation line significant increases could be demonstrated in fibrinogen, fibrin monomers and thrombin-antithrombin III. The fibrinolysis System showed significant increases for Ddimers, tissue pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Perivas cular and intravascular lesions as well as ag gregation of red blood cells are atherogenic and coagulant risk factors; they were de scribed as significantly more frequent in peo ple suffering from stable arterial hypertension with a history of minor brain stroke [ 1 ]. Sever al studies in hypertensive subjects [2][3][4][5][6][7][8] have shown that platelet reactivity was increased with advancing age [9,10], and von Willebrand factor, co-antiplasmin, D-dimer (DD), tissue-type plasminogen activator (t-pA) and plasminogen activator inhibitor (PAI-1) were found to be significantly higher, compared with healthy subjects [2,11]. Furthermore, several studies have shown that various anti hypertensive drug regimens differ in their ef fects on haemostasis [12], These effects could be of importance for their proposed actions on cardiovascular morbidity and mortality [ 13], The present study was aimed at evaluat ing, after 6 and 12 months, the haemostatic effects of an angiotensin-converting enzyme (ACE) inhibitor in a group of patients with essential hypertension, precedently studied, without any evident haemostatic activation [2], At the initial stages of hypertension, the plasma levels of thrombomodulin (TM) as a marker of endothelium damage, (i-thromboglobulin (P-TG) as an indicator of platelet activation, DD which increases in hypercoagulable states, t-PA and PAI-1 were deter mined.…”
Section: Introductionmentioning
confidence: 99%
“…Perivas cular and intravascular lesions as well as ag gregation of red blood cells are atherogenic and coagulant risk factors; they were de scribed as significantly more frequent in peo ple suffering from stable arterial hypertension with a history of minor brain stroke [ 1 ]. Sever al studies in hypertensive subjects [2][3][4][5][6][7][8] have shown that platelet reactivity was increased with advancing age [9,10], and von Willebrand factor, co-antiplasmin, D-dimer (DD), tissue-type plasminogen activator (t-pA) and plasminogen activator inhibitor (PAI-1) were found to be significantly higher, compared with healthy subjects [2,11]. Furthermore, several studies have shown that various anti hypertensive drug regimens differ in their ef fects on haemostasis [12], These effects could be of importance for their proposed actions on cardiovascular morbidity and mortality [ 13], The present study was aimed at evaluat ing, after 6 and 12 months, the haemostatic effects of an angiotensin-converting enzyme (ACE) inhibitor in a group of patients with essential hypertension, precedently studied, without any evident haemostatic activation [2], At the initial stages of hypertension, the plasma levels of thrombomodulin (TM) as a marker of endothelium damage, (i-thromboglobulin (P-TG) as an indicator of platelet activation, DD which increases in hypercoagulable states, t-PA and PAI-1 were deter mined.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, age and BMI are traditional correlates of DD [21,27,28], a commonly used clinical marker of fibrin turnover [4]. Accordingly, we found higher DD levels in hypertensives than normotensives and a trend of association of DD with age (P 0.09).…”
Section: Discussionmentioning
confidence: 56%
“…Excess cardiac morbidity and mortality in subjects with OSA [12] could be explained in part by a hypercoagulable state related to either increased sympathetic nerve activity [18] or co-morbid hypertension [19]. Similarly, systemic hypertension has been associated with a hypercoagulable state [20], as evidenced by increased plasma levels of TAT, DD and vWF [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, alterations in the plasma concentrations of coagulation and fibrinolysis factors are considered the link between diabetes mellitus and cardiovascular complications [7][8][9]. Also, in a hypertensive state, changes in Trifiletti/Lasco/Scamardi/Cincotta/Gaudio/ Barbera/Frisina the balance between hemostatic and antithrombotic processes, inducing a prethrombotic state, may contribute to hypertensive vascular complications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%